An In Vitro and In Vivo Study of the Efficacy and Toxicity of Plant-Extract-Derived Silver Nanoparticles - Anjana S. Desai; Akanksha Singh; Zehra Edis; Samir Haj Bloukh; Prasanna Shah; Brajesh Pandey; Namita Agrawal; Neeru Bhagat (Journal of Functional Biomaterials, 2022)
Silver nanoparticles (AgNPs) display unique plasmonic and antimicrobial properties, enabling them to be helpful in various industrial and consumer products. However, previous studies showed that the commercially acquired silver nanoparticles exhibit toxicity even in small doses. Hence, it was imperative to determine suitable synthesis techniques that are the most economical and least toxic to the environment and biological entities. Silver nanoparticles were synthesized using plant extracts and their physico-chemical properties were studied. A time-dependent in vitro study using HEK-293 cells and a dose-dependent in vivo study using a Drosophila model helped us to determine the correct synthesis routes. Through biological analyses, we found that silver nanoparticles’ cytotoxicity and wound-healing capacity depended on size, shape, and colloidal stability. Interestingly, we observed that out of all the synthesized AgNPs, the ones derived from the turmeric extract displayed excellent wound-healing capacity in the in vitro study. Furthermore, the same NPs exhibited the least toxic effects in an in vivo study of ingestion of these NPs enriched food in Drosophila, which showed no climbing disability in flies, even at a very high dose (250 mg/L) for 10 days. We propose that stabilizing agents played a superior role in establishing the bio-interaction of nanoparticles. Our study reported here verified that turmeric-extract-derived AgNPs displayed biocompatibility while exhibiting the least cytotoxicity.